Penyuluhan Komunikasi Efektif Petugas Kesehatan Dengan Pengguna Jasa Pelayanan Kesehatan (Pasien Atau Keluarga Pasien) - Saadah, Alfina Aisatus; Faida, Eka; Firdaus, Abidatu Zahrotul (STIKES Yayasan RS.Dr.Soetomo, 2024)
A hospital is declared successful if it can provide the best service to its patients. Not only due to the completeness of the existing facilities, but also the attitude and service provided by the human resources at the hospital, this will influence the satisfaction aspect of patients who receive treatment at the hospital. Problems in the communication process that often occur between patients and health workers are the use of vocabulary that is too long, difficult to understand, complex, as well as the use of medical terms that patients often do not understand. The aim of this community service is that participants are able to understand effective communication between health workers and health service users (patients or patient families). The type of community service used is by conducting outreach methods. The target data for this community service activity are STIKES students at Dr. Hospital Foundation. Soetomo Surabaya and students majoring in health from other institutions, both private and state. Based on the results of community service, data was obtained that before the counseling was carried out, the level of understanding of participants in the good category was 25%, in the fair category was 47%, and in the poor category was 28%. Meanwhile, after counseling, the level of understanding of participants in the good category was 71%, in the fair category was 23%, and in the poor category was 6%. Data was obtained from pre-test and post-test questions completed by participants. So it can be concluded that after the counseling was carried out, the level of understanding of the participants changed from being in the adequate category with the largest number to being in the good category. With the enthusiasm of participants in participating in outreach, health facilities and institutions need to provide education and training on effective communication.